2017
DOI: 10.1093/ser/mwx014
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment reduction or labor force expansion? How partisanship matters for the design of active labor market policy in Europe

Abstract: Comparative scholars fundamentally disagree about the impact of partisan politics in modern welfare states, particularly in certain ‘new’ policy areas such as active labor market policy (ALMP). Using new data on 900 ALMP programs across Europe, this study attempts to reconcile a long-standing dispute between the traditional ‘power resources’ approach and the ‘insider/outsider’ approach pioneered by Rueda. The study argues that both left-wing and right-wing governments invest in ALMP but that politics still mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Beyond the role of employers, the welfare regime literature (see Esping‐Andersen, 1990), indicate that political actors affect the extent (Boix, 1998; Nelson, 2013), as well as the composition of spending on ALMP (Cronert, 2019; Iversen & Stephens, 2008). While the aversion to state intervention entails low spending on all types of ALMP in liberal welfare regimes, CMEs are split between Social Democratic regimes (i.e., Nordic countries) and conservative or Christian Democratic regimes (i.e., Continental Europe).…”
Section: Types and Institutional Contexts Of Almpmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the role of employers, the welfare regime literature (see Esping‐Andersen, 1990), indicate that political actors affect the extent (Boix, 1998; Nelson, 2013), as well as the composition of spending on ALMP (Cronert, 2019; Iversen & Stephens, 2008). While the aversion to state intervention entails low spending on all types of ALMP in liberal welfare regimes, CMEs are split between Social Democratic regimes (i.e., Nordic countries) and conservative or Christian Democratic regimes (i.e., Continental Europe).…”
Section: Types and Institutional Contexts Of Almpmentioning
confidence: 99%
“…However, design of programs may also have different effects across target groups, where studies on German administrative data show that sequences of classroom training can be beneficial for long‐term unemployed (Dengler, 2019). While the latter highlights the importance of continued and intensified training, it should also be noted that participation in programs may renew eligibility for unemployment benefits (Cronert, 2019). If that is the case, increases in job‐search intensity may not occur.…”
Section: Disaggregating Almps—theoretical Effects and Previous Evidencementioning
confidence: 99%
“…Turning to ALMP, scholars have recently begun to relax the commonplace assumption that these policies primarily benefit labor market 'outsiders' at the expense of 'insiders', and instead argue that they may actually target rather different groups and consequently come with rather different distributional profiles. For instance, studies have shown that right-wing governments are more positive towards ALMP when such policies partly or exclusively target outsiders, whereas left-wing governments are more prone to expand programs that also target 'insiders' (Cronert, 2019;Gingrich & Ansell, 2015).…”
Section: Who Stands To Benefit From Micro-interventionism?mentioning
confidence: 99%
“…The effect of partisanship on ALMP development has been perhaps the most contested issue in comparative ALMP research over the past decade. 24 In recent years, a new but still inconsistent wave of research has suggested that the role of partisanship varies across categories of ALMP programs. 25 Regarding employment subsidies and other employer-involving programs such as those in focus here, studies support two conflicting hypotheses.…”
Section: Partisan Politics and The Mode Of Production Of Almpmentioning
confidence: 99%